CAPACITY ISSUES IN LOCAL COMMUNITIES FOR INTEGRAL URBAN REGENERATION - Mrđenović, Tatjana J (Arhitektura i urbanizam, 2014)
The subject of the research in wider sence is organizational-communication capacity of local communities in Serbia in the frame of sustainable development. Along with this, the paper will explore potentialities of Faludi’s model of miltiplanning agencies as well as Healey’s collaboritibe theory for better efficiency and effectiveness of planning in the process of urban regeneration. Specifficaly the paper will research relation between organizational structure of local communities in Serbia and their potetnitalities to provide adequate communication towards integral information for urban regeneration. Research is framed with a problem of efficiency and effectiveness in creating urban regeneration policies, strategies, designs, and technical solutions. The problem will be focused to Serbian context; characterized with inadequate, transitional, system of governance that is moving from centralistic towards decentalistic model. This will be further explored through level and type of participation in the process of urban regeneration. The hypothesis of the research explores the nature of the relation between number and types of communication channals, provided by organizational structure of local communities that should enable effectiveness and efficiency of urban regeneration. In other words the hypothesis is: number and types of communication channels (variable A) influences the efectivness and efficiency of urban planning for sustainable urban regeneration (variable B). The aims of the paper are identification of the regulations betweent the variables. Expected result is establishing the model for measuring the capacity of local communities for integral urban regeneration. Key words: sustainable urban regeneration, integral urban planning, capacity of local communities